Myocardial and Microvascular Injury Due to Coronavirus Disease 2019 - Rocco A Montone; Giulia Iannaccone; Maria Chiara Meucci; Filippo Gurgoglione; Giampaolo Niccoli (European Cardiology Review)
Over the past few months, health systems worldwide have been put to the test with the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Even though the leading clinical manifestations of the SARS-CoV-2 infection involve the respiratory tract, there is a non-negligible risk of systemic involvement leading to the onset of multi-organ failure with fatal consequences. Since the onset of COVID-19, patients with underlying cardiovascular disease have been at increased risk of poor clinical outcomes with higher death rates. Moreover, the occurrence of new-onset cardiac complications is not uncommon among patients hospitalised for COVID-19. Of importance, a significant portion of COVID-19 patients present with myocardial injury. Herein, the authors discuss the mechanisms leading to myocardial and microvascular injury in SARS-CoV-2 infection and their clinical implications.